Post-tuberculosis treatment paradoxical reactions - Hermans, Sabine M.; Akkerman, Onno W.; Meintjes, Graeme; Grobusch, Martin P. (Infection, 2024)
Paradoxical reactions (PR) to tuberculosis (TB) treatment are common during treatment, but have also been described after treatment. A presentation with recurrent signs or symptoms of TB after cure or completion of prior treatment needs to be differentiated between microbiological relapse and a paradoxical reaction. We searched all published literature on post-treatment PR, and present a synthesis of 30 studies, focusing on the epidemiology, diagnosis and management of this phenomenon. We report an additional case vignette. The majority of studies were of lymph node TB (LN-TB), followed by central nervous system TB (CNS-TB). A total of 112 confirmed and 42 possible post-treatment PR cases were reported. The incidence ranged between 3 and 14% in LN-TB and was more frequent than relapses, and between 0 and 2% in all TB. We found four reports of pulmonary or pleural TB post-treatment PR cases. The incidence did not differ by length of treatment, but was associated with younger age at initial diagnosis, and having had a PR (later) during treatment. Post-treatment PR developed mainly within the first 6 months after the end of TB treatment but has been reported many years later (longest report 10 years). The mainstays of diagnosis and management are negative mycobacterial cultures and anti-inflammatory treatment, respectively. Due to the favourable prognosis in LN-TB recurrent symptoms, a short period of observation is warranted to assess for spontaneous regression. In CNS-TB with recurrent symptoms, immediate investigation and anti-inflammatory treatment with the possibility of TB retreatment should be undertaken.